The wishing pearl - Harrison, Paula (New York : Scholastic Inc., 2012)
Princess Clarabel and her friends help an injured dolphin during Ampali Island's Royal Regatta.
Appeals to 2nd-3rd graders; reading level, grade 3.
720
Accelerated Reader AR
Keywords: Princesses -- Juvenile fiction; Dolphins -- Juvenile fiction; Animal rescue -- Juvenile fiction